Advances in functional genomics for exploring abiotic stress tolerance mechanisms in cereals - Goche, Tatenda; Mavindidze, Peter; Zenda, Tinashe (Plants, 2025)
Climate change, population growth and the increasing demand for food and nutritional security necessitate the development of climate-resilient cereal crops. This requires first gaining mechanistic insights into the molecular mechanisms underpinning plant abiotic and biotic stress tolerance. Although this is challenging, recent conceptual and technological advances in functional genomics, coupled with computational biology, high-throughput plant phenotyping and artificial intelligence, are now aiding our uncovering of the molecular mechanisms underlying plant stress tolerance. Integrating other innovative approaches such as genome editing, modern plant breeding and synthetic biology facilitates the development of climate-smart cereal crops. Here, we discuss major recent advances in plant functional genomic approaches and techniques such as third-generation sequencing, transcriptomics, pangenomes, genome-wide association studies and epigenomics, which have advanced our understanding of the molecular basis of stress tolerance and development of stress-resilient cereals. Further, we highlight how these genomics approaches are successfully integrated into new plant breeding methods for effective development of stress-tolerant crops. Overall, harnessing these advances and improved knowledge of crop stress tolerance could accelerate development of climate-resilient cereals for global food and nutrition security. Keywords: cereal crops; functional genomics; abiotic stress tolerance; third-generation sequencing; transcriptomics; genome-editing techniques; metagenomics
Keywords: NATURAL SCIENCES::Chemistry::Biochemistry::Functional genomics; Abiotic stress tolerance; Metagenomics; Genome editing techniques